Questioning the Regional Integration of Higher Education in ASEAN: Equality for All? - Dudy Heryadi; Anggia Utami Dewi; Akim Akim; Cecep Hermawan; Waki'ah Waki'ah (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
Regional integration in ASEAN, within the framework of ASEAN Community has three pillars. ASEAN Socio-Culture Community as one of the pillars brought the vision of equality of access toward education aligned with the United Nation Sustainable Development Goals. Specifically, integration higher education is institutionally spearheaded by the ASEAN University Network (AUN) established in 1995, which currently is still the only legitimate HEI’s platform under the ASEAN Secretariat. This paper discusses the question on the exclusivity of AUN membership that had created the narratives of doubt among the non-member universities of AUN. The research is conducted with the qualitative methods in triangulation design based on the primary data taken from in-depth interview and structured focus group discussion (FGD), supplemented by the desk study on current research on the area of regional integration and higher education management. The result presented the positive view on the question posed in the research. AUN is adapting to change, with several universities are now holding the status of associate membership. AUN also stated that they are under the preparation of making scheme and procedure of new membership application. As a unique space of integration in ASEAN, AUN is continuously adjusting to accommodate the needs of the greater audience.Keywords—higher education, ASEAN University Network, inclusive, regional integration, ASEAN